The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.3390/ijms222011196
|View full text |Cite
|
Sign up to set email alerts
|

Novel Cardiovascular Risk Factors in Patients with Diabetic Kidney Disease

Abstract: Patients with diabetic kidney disease (DKD) are at very high risk for cardiovascular events. Only part of this increased risk can be attributed to the presence of diabetes mellitus (DM) and to other DM-related comorbidities, including hypertension and obesity. The identification of novel risk factors that underpin the association between DKD and cardiovascular disease (CVD) is essential for risk stratification, for individualization of treatment and for identification of novel treatment targets.In the present … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
2
0
2

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 107 publications
(119 reference statements)
1
2
0
2
Order By: Relevance
“…In addition, the results of this study showed that age, male gender, diabetic duration, HbA1c levels and high blood pressure were also risk factors for DKD, which is consistent with previous research [ 32 , 33 , 34 ]. Furthermore, the multivariate predictive model was established with DKD as the dependent variable and sex, age, BMI, diabetic duration, BP, HbA1c levels and FT3/FT4 as independent variables.…”
Section: Discussionsupporting
confidence: 93%
“…In addition, the results of this study showed that age, male gender, diabetic duration, HbA1c levels and high blood pressure were also risk factors for DKD, which is consistent with previous research [ 32 , 33 , 34 ]. Furthermore, the multivariate predictive model was established with DKD as the dependent variable and sex, age, BMI, diabetic duration, BP, HbA1c levels and FT3/FT4 as independent variables.…”
Section: Discussionsupporting
confidence: 93%
“…5,6 Patients with DKD are at higher risk of cardiovascular disease (CVD) and end-stage renal disease (ESRD), leading to a significant increase in all-cause mortality and overall medical costs. 7,8 From 2000 to 2015, the proportion of ESRD patients with DM increased from 19.0% to 29.7%, and the annual incidence increased from 375.8 per million people to 1016 per million people. 9 The overall prognosis of DM patients with DKD is poor and the mortality rate is high.…”
Section: Introductionmentioning
confidence: 99%
“…The results of the study are in general agreement with Reddy et al 17 In addition, the incidence of adverse cardiac events in patients with AVF was higher than that in patients with CVC (P<0.05), suggesting that in patients undergoing MHD, AVF has a stronger negative impact on the cardiac function than CVC, which supported the findings by Faull et al 18 and Stoumpos et al 19 We may speculate that, since 42.59% of the patients in our cohort had diabetes nephropathy and 31.48% had hypertension nephropathy, these conditions may lead to abnormal left ventricular function in both groups. 20,21 Additionally, AVF access adversely affects the heart because of the increased workload required for vascular access blood flow. 22 Blood passes through the AVF faster than through a typical blood vessel, and the increased blood flow makes the heart pump harder, resulting in long-term stress on the heart that can lead to left ventricular hypertrophy and eventually cause ventricular systolic dysfunction.…”
Section: Discussionmentioning
confidence: 99%